Analysis of the possibility of using household sewage sludge inagricultural production (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
An analysis of various treatment facilities that treat domestic wastewater leads to the conclusion that any wastewater treatment technology produces sediment that is sent to sludge fields, which are the most problematic part of biological wastewater treatment. Fields of accumulation of semi-liquid mass are often overloaded three times, and sometimes even more. This situation is connected with the fact that projects of sewage treatment plants for large cities were developed in 1970-1980, without taking into account the rapid development of cities.The problem of agricultural production in Ukraine is soil depletion. In particular, this is the effect of wind and water erosion. At the same time, losses of humus due to mineralization and soil erosion amount to 32-33 million tons annually, which is equivalent to 320-330 million tons of organic fertilizers.Another problem of the agricultural sector of our country is the large amount of nongrain part of the harvest (straw). The correct combination of a large amount of sludge from sewage treatment plants and the non-cereal part of the harvest will make it possible to disinfect the sludge and obtain organic fertilizers through composting, which will restore the fertility of soils, in particular, of agricultural production in Ukraine.
Keywords: гумус; cleaning; disinfection; composting; organic fertilizers; humus